What Still Needs to be Noted: Pseudo-Clefts in the Academic Discourse of Applied Linguistics - Zhou, Hui; Chen, Ming (Frontiers in Psychology, 2021)
Pseudo-clefts are building blocks of coherent discourse progression, and a rhetorical toolkit to construct authorial stance in the academic discourse. Despite an increasing interest in grammatical constructions in academic discourse, researchers have not treated pseudo-clefts in much detail. This paper explores the features of pseudo-clefts in the corpus of academic discourse in the field of applied linguistics. Here we take the textual and the interpersonal perspectives, focusing on the use of pseudo-clefts in terms of its distribution in generic structure, discourse functions with reference to clefted constituents, and evaluative meaning. The results show that pseudo-clefts were more frequently used in Results and discussion and Literature review, performing the functions such as specification of key terms, generalization of literature, description and explanation of findings, etc. They are facilitative in creating information gap and establishing a logic-semantic expansive relationship between clauses. The findings also suggest that pseudo-clefts are evaluative devices and they are involved in the construction of authorial identities.